Comparative study of fuel economy and emissions for plug-in hybrid electric Payang Water Taxi on different driving cycles using ADVISOR - Ahmad Luqmanul Hakim Ahmad Tarmizi; Siti Norbakyah Jabar; Salisa Abdul Rahman (Institute of Advanced Engineering and Science, 2026)
A new conceptual series-parallel plug-in hybrid vehicle for water transportation, known as the plug-in hybrid electric Payang Water Taxi (PHEPWT), is designed to improve vehicle fuel economy and significantly lower boat emissions. This article aims to analyze the fuel economy and emissions of PHEPWT, which are Hydrocarbons (HC), Carbon Monoxide (CO), and Nitrogen Oxides (NOx), with 6 driving cycles including Pulau Warisan river route, Kuala Terengganu river route, Kampung Laut river route, Seberang Takir river route, Pulau Kapas river route, and Tasik Kenyir river route. The analysis of the PHEPWT model will be compared with the existing powertrain architectures using water drive cycles by using the advanced vehicle simulator (ADVISOR). The results will be expected based on the fuel economy and emissions analysis that will show about 30-50% improvement in driving cycle for each driving cycle, and the fuel economy of the PHEPWT will indicate about 15-20% higher than that of the ADVISOR model. Also, for emission, the PHEPWT and ADVISOR models are based on the result of three-type emission such as HC, CO, and NOx, and show that the PHEPWT model has a lower emission compared to the ADVISOR model.